AN INVESTIGATION OF THE EVOLUTION OF SMES' DIGITAL ACCOUNTING PRACTICES: AN UTAUT FRAMEWORK ANALYSIS ON BEHAVIORAL CHANGES MODERATED BY COVID-19 - Ranatarisza, Mirza Maulinarhadi; Tjaraka, Heru; Rahmiati, Alfa (Jurnal Manajemen dan Kewirausahaan, 2025)
This study examines how COVID-19 pandemic conditions moderate the relationship between behavioral intention and use behavior in SME accounting application adoption. Using the UTAUT framework, we surveyed 366 Indonesian SMEs during and after the pandemic, analyzing data through PLS-SEM. Results confirm that Performance Expectancy (β=0.38), Effort Expectancy (β=0.15), Social Influence (β=0.26), and Facilitating Conditions (β=0.11) significantly influence Behavioral Intention, which mediates their effects on Use Behavior. Surprisingly, the pandemic period weakened rather than strengthened the intention-behavior relationship (β=-0.15, p<0.01), revealing a digital readiness gap between intention formation and execution capability. This finding challenges assumptions about crisis-driven technology adoption and suggests that external shocks may hinder rather than accelerate meaningful digital transformation in resource-constrained SMEs. Implications include need for staged implementation approaches and infrastructure development beyond training initiatives.